Tourism Business in a VUCA World: Marketing and Management Implications - LUBOWIECKI-VIKUK, Adrian; SOUSA, Bruno (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021, 2021)
In the context of modern management, we referred to the re-creation of tourism products, modification of segments, and directions of marketing tourism enterprises and destinations development. The COVID-19 crisis should thus be seen as an opportunity to critically reconsider tourism’s growth trajectory, and to question the logic of more arrivals implying greater benefits. As a result of the COVID-19 pandemic, the tourism industry went from over-tourism to ‘no tourism’. We paid attention to the implementation of the EFE concept (education, flexibility, empathy) and the necessary marketing segmentation. This manuscript aims to further develop the understanding of the marketing involvement for tourism business in a volatile, uncertain, complex, and ambiguous (VUCA) world. Implications for future research are also presented.